A Redescription of Thermocyclops uenoi (Crustacea, Copepoda) - Mirabdullayev, I.M.; Ueda, H. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Thermocyclops uenoi Ito, 1952, a poorlyknown groundwater species is redescribed based on the materials of collection Dr. T. Mizuno. A key to Japanese species of the genus Thermocyclops is provided. Thermocyclops uenoi Ito, 1952, малоизвестный подземный циклоп, переописан по материалам коллекции Т. Мицуно. Составлена таблица для определения видов рода Thermocyclops фауны Японии.